The Law Enforcement of Environmental Law against Illegal Mining - Harinda, Khoirulika Nur; Purnawan, Amin; Witasari, Aryani (Law Development Journal, 2021)
The purpose of this study is to identify and analyze law enforcement against illegal mining in Indonesia. Based on the results of the study, it can be concluded that illegal mining law enforcement is an unlawful act, regulated by Act No. 4 of 2009 concerning Mineral and Coal Mining, the threat of punishment is regulated from Articles 158 to 165. Administrative law enforcement in illegal mining crimes by the authority law enforcement is carried out in a preventive manner. Supervision in law enforcement of mining administration in a limited manner has been regulated as stipulated in the provisions of Article 39, Article 78 and Article 79 concerning Mining Business Permits (IUP) or Special Mining Business Permits (IUPK). The signs contained in the Mining Business Permit (IUP) or Special Mining Business Permit (IUPK), are obligations that must be carried out by the recipient of the Mining Business Permit (IUP) or Special Mining Business Permit (IUPK), and if a violation is committed, the official who issuing the permit has the right to impose sanctions. Based on this suggestion, it is hoped that there will be coordination and integration between relevant agencies, in particular to carry out socialization activities for legal counseling regarding Act No. 4 of 2009.